Differentiated Learning in Islamic Religious Education: A Literature Review of Concepts, Principles, and Implementation - Hana Ayu Safitri; Mahasri Shobahiya; Mohamad Ali; Nurul Asma Khoiriyah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
PAI learning in schools still tends to be uniform and teacher-centered, so it is not fully able to accommodate individual differences of students. In the context of the Independent Curriculum, differentiated learning is a relevant approach because it is in line with the spirit of "independent learning" and Islamic values such as justice ('adl), compassion (rahmah), and responsibility (amanah). The purpose of this study is to examine the concepts, principles, and implementation of differentiated learning in PAI based on theoretical reviews and scientific literature, as well as analyze the relevance of this approach to the development of students' Islamic character and values. This research uses a qualitative method with a library research approach . Data was obtained from various written sources such as books, scientific articles, academic journals, and the results of previous research that discussed the concept of differentiation in the context of Islamic education. The results of the study show that differentiated learning in PAI can be applied through three main strategies, namely content, process, and product differentiation. This strategy allows teachers to adjust the material, methods, and forms of evaluation according to students' abilities and interests. Islamic principles such as justice, compassion, and responsibility become the theological foundation in its implementation, so that learning not only improves academic results, but also shapes the spiritual and moral character of students. The main obstacles to the implementation of this approach include the limitations of teacher competence, infrastructure, and the learning paradigm that is still teacher-centered. Therefore, continuous training, collaboration between educators, and learning innovations are needed to support optimal implementation. differentiated learning in Islamic Religious Education makes a significant contribution to the creation of an adaptive, humanist, and learning process based on Islamic values. This approach not only increases the effectiveness of learning, but also strengthens the purpose of Islamic education in forming a generation of faithful, knowledgeable, and noble character.